1943
DOI: 10.5254/1.3540101
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight and Accelerated Light Aging of Synthetic Rubbers

Abstract: Recently Werkenthin, Richardson, Thornley and Morris reported on the sunlight and accelerated light aging of various natural and synthetic rubber stocks, and proposed a method for standardizing the accelerated light aging test. The purpose of the present paper is to provide data on the correlation of sunlight aging with accelerated light aging for various synthetic rubber stocks loaded with mineral pigments. FORMULAS AND CURES The formulas and cures for the synthetic rubber stocks are given in Table I. These s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1946
1946
1952
1952

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Buna N Rx. Natural rubber neoprene vulcanizates to deterioration by atmospheric ozone during outdoor weathering is particularly outstanding (3,8,10,11). The type of surface cracking attributable to ozone attack, which so often results in the failure of less resistant elastomers exposed to weathering, does not appear on properly compounded neoprene vulcanizates even after long outdoor exposure.…”
Section: Butylmentioning
confidence: 99%
“…Buna N Rx. Natural rubber neoprene vulcanizates to deterioration by atmospheric ozone during outdoor weathering is particularly outstanding (3,8,10,11). The type of surface cracking attributable to ozone attack, which so often results in the failure of less resistant elastomers exposed to weathering, does not appear on properly compounded neoprene vulcanizates even after long outdoor exposure.…”
Section: Butylmentioning
confidence: 99%
“…This was first realized by the Bureau of Ships of the Navy Department; early in 1942 this bureau urged full cooperation between rubber manufacturers and interested government agencies to provide information on the compatibility of various types of guayule rubbers with Hevea rubber, -with various types of reclaimed rubber, and with all of the available synthetic rubbers. When Mexican or domestic resinous and deresinated guayule rubbers were substituted for GR-S to the extent of 20%, a striking improvement in processability, tack, tear resistance, and cut growth was observed by Morris and co-workers (10,11, IS). Carlton and Reinbold (7) showed that a blend of 25% Hevea and 75% GR-S had considerably better building tack, tensile strength, elongation, and tear resistance, and less heat build-up, than GR-S alone.…”
mentioning
confidence: 98%